The effect of liquidity, credit risk, firm size, and capital structure on the profitability of Islamic commercial banks registered with the OJK for the period 2020-2023 - Susi Wijayanti; RA Sista Paramita (Universitas Negeri Surabaya, 2025)
Banks are one of the sectors that are very important for the economic development of a country, so bank management must be done well. The success of bank management can be assessed from the level of profit earned. This study aims to analyze the effect of liquidity, credit risk, firm size, and capital structure on the profitability of Islamic Commercial Banks Registered in OJK for the period 2020-2023. The data used in this study are quantitative data sourced from secondary data. The population studied was Islamic Commercial Banks Registered in OJK during the period 2020-2023. The sampling method used was purposive sampling. The analysis technique used is multiple linear regression analysis with the help of IBM SPSS software version 25. The results showed that the liquidity variable had a significant positive effect on profitability, while the credit risk variable, firm size, and capital structure had a significant negative effect on profitability.